2014
DOI: 10.1080/1091367x.2014.912985
|View full text |Cite
|
Sign up to set email alerts
|

Estimating VO2max Using a Personalized Step Test

Abstract: The purpose of this study was to develop a personalized step test and a valid regression model that used non-exercise data and data collected during the step test to estimate VO 2 max in males and females 18 to 30 years of age. All participants (N= 80) successfully completed a step test with the starting step rate and step height being determined by the self-reported perceived functional ability (PFA) score and participant's height, respectively. All participants completed a maximal graded exercise test (GXT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
1
8
0
1
Order By: Relevance
“…Legend: Results are expressed as mean ± standard deviation. a significantly different from CON of the same sex (p < 0.05), b significantly different from CON of the same sex (p < 0.01), c significantly different from CON of the same sex (p < 0.0001) Paterson, 2001;Santo & Golding, 2003;Sykes & Roberts, 2004;Webb, Vehrs, George, & Hager, 2014). In our study we found a significant relationship between estimated and measured VO 2 max for the total sample, with R 2 0.24 for AHraw and 0.36 for AHcomplete.…”
Section: Statisticssupporting
confidence: 43%
“…Legend: Results are expressed as mean ± standard deviation. a significantly different from CON of the same sex (p < 0.05), b significantly different from CON of the same sex (p < 0.01), c significantly different from CON of the same sex (p < 0.0001) Paterson, 2001;Santo & Golding, 2003;Sykes & Roberts, 2004;Webb, Vehrs, George, & Hager, 2014). In our study we found a significant relationship between estimated and measured VO 2 max for the total sample, with R 2 0.24 for AHraw and 0.36 for AHcomplete.…”
Section: Statisticssupporting
confidence: 43%
“…Culpepper and Francis 16 proposed equations for healthy men and women taking into account both the individuals' height and hip flexion angle to estimate the ideal step height; with this, the energy expenditure resulting from biomechanical inefficiency during the test is reduced, and the test is standardized for each individual. Webb et al 35 used the same equation with individualized step heights and concluded that the four-minute test performed in fixed cadence provided an accurate estimate of the aerobic capacity in healthy individuals. In our study, an average step height value of 32 centimeters was obtained from the aforementioned equation.…”
Section: Discussionmentioning
confidence: 99%
“…e mask was fixed to the head with adjustable straps. e CORTEX ergospirometer model MetaLyzer® 3B (Germany) reported the data in real time, breath by breath, and was used to determine the VO 2 max, under the following criteria: respiratory exchange ratio (RER) ≥1.11 (Hamlin et al, 2012;Web et al, 2014), an HR ≤ 10 beats . min -1 or ≤ 5% in respects to the maximum estimated (220-age) (Poole & Jones, 2017).…”
Section: Instruments and Proceduresmentioning
confidence: 99%